UPAYA MENINGKATKAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN MODEL PJBL PADA MATA PELAJARAN PKN KELAS III DI SDN 104211 MARINDAL KECAMATAN MEDAN AMPLAS - Ratih Wulandari; Ulian Barus (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This research aims to determine the improvement in Civics learning outcomes on theme 1 (growth and development of living things) sub-theme 1 (characteristics of living things) in class III students at SDN 104211 Marindal in the 2023 academic year. This research is a type of classroom action research (CAR). ) which consists of three cycles and four stages. Each cycle includes planning, implementation, observation and reflection. This stage is a cycle that takes place repeatedly and is carried out with the same steps and is focused on the project based learning (PjBL) learning model. The subjects of this research are teachers (researchers) who conduct research in implementing the project based learning (PjBL) learning model. The data collection technique used is observation while students are following the learning process and using tests in the form of questions carried out at the end of the cycle as well as documentation during learning activities. The results of this research show that there is an increase in students' Civics learning outcomes using the project based learning (PjBL) learning model in each cycle. This increase can be seen looking at the cycles that have been carried out. In the first cycle, student learning outcomes reached 65.38% of 26 students, only 17 students completed. Furthermore, in cycle II there was an increase in learning outcomes reaching 76.92% completeness and only 6 were incomplete. Furthermore, in cycle III there was an increase in learning outcomes reaching 92.30% and only 2 were incomplete. The conclusion of this research is that efforts to use the project based learning model can improve Civics learning outcomes for class III students at SDN 104211 Marindal.